A comparison of balloon angioplasty of native coarctation versus surgical repair for short segment coarctation associated with ventricular septal defect—a single-center retrospective review of 92 cases - Zhang, Huifeng; Ye, Ming; Chen, Gang; Liu, Fang; Wu, Lin; Jia, Bing (Journal of Thoracic Disease, 2016)
Background: The hybrid technique combining balloon angioplasty for discrete coarctation (CoA) and surgical repair of a ventricular septal defect (VSD) is a novel treatment for patients with aortic CoA and VSD, but the efficacy of this approach is unknown. Methods: We performed a retrospective analysis of 92 patients with short segment CoA and VSD who underwent complete repair between January 2004 and July 2014 in our center. Patients were divided into two groups according to the surgical approach employed: hybrid procedure (group A, n=39) and traditional midline surgical repair (group B, n=53). Baseline, perioperative, and outcome data were compared between the two groups. Results: Three early deaths occurred in group B, whereas none occurred in group A. Compared to those in group B, patients in group A experienced a shorter aortic clamp duration (28.1±6.7 vs. 43.2±9.2 minutes, P